Final Year Students' Knowledge on Basic Manual Wheelchair Provision: The State of Occupational Therapy Programs in Colombia. (29th April 2020) - Toro-Hernández, María L.; Alvarez, Liliana; Vargas-Chaparro, María C.; Goldberg, Mary
Abstract : Access to personal mobility is a human right and as such, it implies the provision of wheelchair services for those with mobility impairments that need one. Lack of appropriately trained personnel is a major contributor to the gap in access to wheelchairs. Assistive technology provision is one of the core competencies of occupational therapists. The goal of this study was to assess the current wheelchair provision knowledge of final year occupational therapy students in Colombia as measured by the International Society of Wheelchair Professionals Basic Wheelchair Service Knowledge Test. A total of 83 students from 7 universities took the test. None of the students met the 70% passing threshold. The highest scores were in the assessment domain while the lowest in the fitting and user training domains. These results suggest that the current wheelchair provision education received in these programs do not meet the World Health Organization guidelines on appropriate wheelchair provision. The implementation of strategies to improve current wheelchair provision education in Colombian occupational therapy programs is granted.